Interrelationships among age at adiposity rebound, BMI during childhood, and BMI after age 14 years in an electronic health record database - Freedman, David S; Goodwin-Davies, Amy J; Kompaniyets, Lyudmyla; Lange, Samantha J; Goodman, Alyson B; Phan, Thao-Ly Tam; Rao, Suchitra; Eneli, Ihuoma; Forrest, Christopher B (Obesity (Silver Spring, Md.), 2022)
This study compared the importance of age at adiposity rebound versus childhood BMI to subsequent BMI levels in a longitudinal analysis. From the electronic health records of 4.35 million children, a total of 12,228 children were selected who were examined at least once each year between ages 2 and 7 years and reexamined after age 14 years. The minimum number of examinations per child was six. Each child's rebound age was estimated using locally weighted regression (lowess), a smoothing technique. Children who had a rebound age < 3 years were, on average, 7 kg/m heavier after age 14 years than were children with a rebound age ≥ 7 years. However, BMI after age 14 years was more strongly associated with BMI at the rebound than with rebound age (r = 0.57 vs. -0.44). Furthermore, a child's BMI at age 3 years provided more information on BMI after age 14 years than did rebound age. In addition, rebound age provided no information on subsequent BMI if a child's BMI at age 6 years was known. Although rebound age is related to BMI after age 14 years, a child's BMI at age 3 years provides more information and is easier to obtain.